Sistem Kendali Terpusat Penjadwalan Perangkat Air Conditioner Berbasis Internet of Things - Daniel Felix Setiawan; Laurentius Kuncoro Probo Saputra; Yuan Lukito (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Air Conditioner (AC) devices in Duta Wacana Christian University 2nd floor Agape computer laboratory are turned on in the morning and turned off in the evening manually by the computer laboratory officer every day after all the classes are over. Whereas there are sessions when laboratory rooms are not used, but the AC is still on. So, there is a waste of electricity. It wastes time and energy in vain. Therefore, the implementation of AC control and scheduling can be the solution. The implementation includes a program for PC that is used to control the AC and IR module that is attached to the computer laboratory’s AC. IR module consists of NodeMCU ESP8266 microcontroller and IR LED. All microcontrollers are connected to the internet over a WiFi network. The microcontroller substitutes conventional remote control. From the result, it can be concluded that the AC control and scheduling system is successfully implemented and worked well with good performance. After the system is implemented, computer laboratory officers no longer need to turn on and off the AC manually every day. Therefore, it can save energy and time. Besides that, waste of electrical energy can be minimized, because AC will turn off automatically when the laboratory room is not used.